Is there a link between problem-based learning and emotional intelligence? - Evans, P (Kathmandu University Medical Journal, 2009)
A brief description of problem-based learning is given and reference is made to the difficulties in demonstrating its value in terms of ‘accumulated knowledge’ with respect to the literature. The author suggests that problem-based learning may be a suitable curriculum component for developing a student’s emotional intelligence. Key words: Emotional intelligence, medical undergraduate, problem-based learning doi: 10.3126/kumj.v7i1.1756 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 4-7